Gender roles and intimate partner violence: a multicultural systematic analysis - Azmi, Filza Izzyan; Hassan, Siti Aishah (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
Intimate partner violence is an aggressive behaviour within an intimate relationship whereby it can cause physical, sexual and psychological harm. One of the factor leading to it is gender roles. This article is a systematic review study which explores the relationship or the roles of gender roles that lead to intimate partner violence. This study is reviewed on a multicultural basis whereby all the journals selected were from different countries. Electronic database was used to search appropriate materials and 10 journals were found. The roles of gender roles on intimate partner violence were compared between cultures and discussed systematically.